Longitudinal gradient in the structure of fish assemblage in a accumulation reservoir: Capivari (Research, Society and Development, 2021)
The present study evaluated the hypothesis that the fish assemblage of Governador Pedro Viriato Parigot de Souza Hydroelectric Power Plant reservoir (Capivari) is longitudinally structured, forming two or three distinct zones. Fish and abiotic variables were collected quarterly between January 2004 and October 2008 at three locations (dam, intermediate and backwater) along the reservoir. A total of 38,085 fishes were captured, which were summarized with non-metric multidimensional scaling (NMS) and compared longitudinally with the permutational multiresponse procedure (MRPP). The occurrence of species distributed in each location was also analyzed. Next, the gradients of variation on fish assemblage structure associated with the abiotic variables were extracted under the linear restriction imposed by them, through the canonical correspondence analysis (CCA). The differences between pure and restricted gradients were evaluated using the Mantel test. The NMS analyses and the MRPP test showed that the pure gradients of fish assemblage structure were longitudinally differentiated, the backwater being different from the others, with a greater preference of species for this location. CCA analyses demonstrated influence of water transparency, pH and dissolved oxygen, so as NMS results. It was concluded that fish assemblage structure in Capivari reservoir presented a zonation pattern, forming two distinct zones in the longitudinal gradient, where was verified that the species has a greater preference for the riverine zone (backwater), mainly influenced by the lower values ​​of water transparency and higher levels of pH and dissolved oxygen.